Thomas & friends. The Christmas letter express [videorecording (DVD)] (NCircle Entertainment, 2024)
Percy has finished delivering holiday gifts all over the island-- only to discover a kid's letter to Santa has got stuck in his mail car! Percy is determined to make things right, even if that means tracking down Mr. Claus himself!